2020
DOI: 10.1074/jbc.ra120.013366
|View full text |Cite
|
Sign up to set email alerts
|

IACS-010759, a potent inhibitor of glycolysis-deficient hypoxic tumor cells, inhibits mitochondrial respiratory complex I through a unique mechanism

Abstract: The small molecule IACS-010759 has been reported to potently inhibit the proliferation of glycolysis-deficient hypoxic tumor cells by interfering with the functions of mitochondrial NADH-ubiquinone oxidoreductase (complex I) without exhibiting cytotoxicity at tolerated doses in normal cells. Considering the significant cytotoxicity of conventional quinone-site inhibitors of complex I, such as piericidin and acetogenin families, we hypothesized that the mechanism of action of IACS-010759 on complex I differs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 63 publications
1
65
1
Order By: Relevance
“…As shown in Figure 4B, all nine inhibitors induced a dose-dependent decrease in the clonogenicity of ES-2 cells. However, only IACS-010759 (Tsuji et al, 2020) and dapagliflozin (Nasiri et al, 2019) displayed selectivity for ES-2 cells where ARID1A has been knocked down. Of these two, IACS-010759 showed a much higher potency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4B, all nine inhibitors induced a dose-dependent decrease in the clonogenicity of ES-2 cells. However, only IACS-010759 (Tsuji et al, 2020) and dapagliflozin (Nasiri et al, 2019) displayed selectivity for ES-2 cells where ARID1A has been knocked down. Of these two, IACS-010759 showed a much higher potency.…”
Section: Resultsmentioning
confidence: 99%
“…IACS-010759 is a clinical-grade small-molecule inhibitor of the Complex I of the electron transport chain (Molina et al, 2018). IACS-010759 has been shown to selectively kill tumor cells that depend on OXPHOS both, in vitro and in preclinical models of human cancers with no cytotoxicity at tolerated doses in normal cells (Bajpai et al, 2020; Fischer et al, 2019; Lissanu Deribe et al, 2018; Molina et al, 2018; Panina et al, 2020; Sun et al, 2019; Teh et al, 2020; Tsuji et al, 2020; Vashisht Gopal et al, 2019; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Photoaffinity labeling experiments have shown that IACS-010759 binds to membrane subunit ND1 of complex I. 213 Another study also suggested that the complex I-binding site of IACS-010759 is at the ND1 subunit as H292 cell clones containing a Leu55Phe mutation in the ND1 subunit showed lower susceptibility to IACS-010759. This suggests that Leu55, which is located at the proposed ubiquinone access channel, is likely involved in the mechanism of inhibition.…”
Section: Targeting Signaling Pathways In Amlmentioning
confidence: 99%
“… 212 IACS-010759 was derived from BAY 87–2243, which is an agent that specifically suppressed HIF-1 target gene expression through inhibition of complex I. 213 Like other complex I and ETC inhibitors studied, BAY 87–2243 was cytotoxic to normal cells, limiting its use in clinical application. BAY 87-2243 failed phase I clinical trials due to dose-limiting toxicities, highlighting the barrier to application of these inhibitors as therapies.…”
Section: Targeting Signaling Pathways In Amlmentioning
confidence: 99%
See 1 more Smart Citation